Prospective Evaluation of Local Sustained Release of Celecoxib in Dogs with Low Back Pain - Tijn Wiersema; Anna R. Tellegen; Martijn Beukers; Marijn van Stralen; Erik Wouters; Mandy van de Vooren; Nina Woike; George Mihov; Jens C. Thies; Laura B. Creemers; Marianna A. Tryfonidou; Björn P. Meij (MDPI AG, 2021)
Back pain affects millions globally and in 40% of the cases is attributed to intervertebral disc degeneration. Oral analgesics are associated with adverse systemic side-effects and insufficient pain relief. Local drug delivery mitigates systemic effects and accomplishes higher local dosing. Clinical efficacy of intradiscally injected celecoxib (CXB)-loaded polyesteramide microspheres (PEAMs) was studied in a randomized prospective double-blinded placebo controlled veterinary study. Client-owned dog patients suffering from back pain were treated with CXB-loaded (n = 20) or unloaded PEAMs ("placebo") (n = 10) and evaluated by clinical examination, gait analysis, owners' questionnaires, and MRI at 6 and 12 weeks follow-up. At 6 and 12 weeks, CXB-treated dogs experienced significantly less pain interference with their daily life activities compared to placebo. The risk ratio for treatment success was 1.90 (95% C.I. 1.24-2.91, p = 0.023) at week 6 and 1.95 (95% C.I. 1.10-3.45, p = 0.036) at week 12. The beneficial effects of CXB-PEAMs were more pronounced for the subpopulation of male dogs and those with no Modic changes in MRI at inclusion in the study; disc protrusion did not affect the outcome. It remains to be determined whether intradiscal injection of CXB-PEAMs, in addition to analgesic properties, has the ability to halt the degenerative process in the long term or restore the disc.